Examining Malaysian secondary school teachers’ perceptions of mathematics education using Q-methodology approach - Memariani, Zahra (2013)
Within constructivist theory framework, this study aimed to provide a clearer focus on factors that contribute to the process of teaching and learning mathematics using Q-methodology approach. Q-methodology provides systematic means to investigate personal beliefs by collecting a concourse, developing a Q-sample, identifying P-sample, conducting a Q-sort process and analyzing of collected data. Forty-seven mathematics teachers in secondary level from Selangor State in Peninsular Malaysia participated in this study.The central research questions addressed in this study are: (a) What are teachers' perception on factors that influence teaching and learning of secondary mathematics? (b) Which factor most influence teaching and learning of secondary mathematics? (c) What are the influence of human factors such as, student individual difference, motivation, teacher enthusiastic and experience, community and family on teaching and learning of secondary mathematics? (d) What are the influences of academic factors such as, curriculum, instructional practice, and technology on teaching and learning of secondary mathematics? (e) What are the relationships between the identified factors? Using previous literature, a concourse was developed. The P-sample of mathematics teachers sorted various statements into categories of most definitely influencing to most definitely not influencing factor. Factor analysis including varimax rotation was completed. Four factors emerged from the Q-methodology procedures indicating shared perceptions among the secondary mathematics teachers. These four factors were: technology and student motivation, student individual differences and family, student motivation and community, family and community. In addition, factors such as community and student motivation were the most important factors in teaching and learning mathematics. Also factors such as student individual difference, family, and technology were emphasized by teachers as important factor in teaching and learning mathematics.Recommendations for future professional improvement include integration of collaborative learning and encouragement among student to use technology in order to enhance the interest of the students and make them attentive in the class.